Análisis del rol femenino dentro de las publicidades difundidas en redes sociales - Valenzuela Andrade, Micaela Naommy (2023)
This research focused on the analysis of the female role within the advertising disseminated on business social networks, with the aim of showing the representation of women in the advertising campaigns of five leading companies, which were (Supermaxi, SC Johnson, Club, Nestlé and Palmolive) broadcast on digital platforms. Specific seasons were taken as a reference, such as Christmas, Valentine's Day and Women's Day, taking the first week before and after each of the mentioned seasons as antecedent. The continuous information is based on a content analysis and observation of these posts on the Instagram and Facebook platforms. The different approaches used to represent women are examined, covering traditional roles or gender stereotypes. Likewise, the interaction is analyzed, in addition to the reactions of the audience to evaluate the perception of the ads, the use of specific colors to show the woman. The results reveal a significant change in the representation of women in digital advertising, showing trends towards a diverse image of women. However, there are still challenges to eliminate stereotypes and, in turn, promote promotion within equitable representation. This underlies the need for a more equitable and diverse description, as well as providing a greater opportunity to demonstrate the physical attributes, as well as the intellectual attributes of women